Influences on the Material Displacement and Compression Stresses in the Joining Process of Highly Viscous Thermal Interface Materials - Gilich, Julian; Teutenberg, Dominik; Meschut, Gerson; Gröger, Benjamin; Wiebicke, Felix; Koch, Ilja; Gude, Maik (77th IIW Annual Assembly and International Conference on Welding and Joining)

In-situ computed tomography and transient dynamic analysis – failure analysis of a single-lap tensile-shear test with clinch points - Reschke, G; Köhler, D; Kupfer, R; Troschitz, J; Gude, M; Brosius, A (Proceedings of the Institution of Mechanical Engineers, Part E: Journal of Process Mechanical Engineering)
Clinching is a mechanical joining technology, in which a mainly form-fit joint is created by means of local cold forming. To characterize the load-bearing behavior of such joints, they are typically analyzed destructively, for example by tensile-shear tests in combination with metallographic sections. However, both the initiation and progress of failure can only be described to a limited extent by this method. Furthermore, these tests allow only limited conclusions about clinch points under in-service loading. More purposefully, clinch points can be analyzed nondestructively by combining in-situ computed tomography (CT) and transient dynamic analysis (TDA). The TDA continuously measures the dynamic behavior of the specimen and indicates failure events like crack initiation, which then can be evaluated thoroughly by stopping the test and performing a CT scan. To qualify the TDA for this task, it is necessary to link the observed damage behavior with specific dynamic characteristics. In this work, the complementation of in-situ CT and TDA is investigated by testing a clinched single-lap tensile-shear specimen made of aluminum. The testing procedure is stepwise: at certain displacement levels, the specimen is investigated by in-situ CT and TDA. While the in-situ CT provides the location, extent, and development of the failure phenomena, the TDA uses this information to evaluate the dynamic signal and detect relevant frequency ranges, which indicate damage events. The results demonstrate, that failure initiation and progression can be analyzed efficiently by combining both measuring systems. The TDA reliably detects relevant signal changes in the monitored frequency band. By means of in-situ computed tomography, the corresponding failure phenomena can be described in detail, enhancing the understanding of the load-bearing and deformation behavior of clinch points. The concatenation of characteristic signal changes and observed failure phenomena can henceforth be transferred to analyze complex structures during operation nondestructively by TDA.

In-situ computed tomography analysis of the failure mechanisms of thermomechanically manufactured joints with auxiliary joining element - Borgert, T; Köhler, D; Wiens, E.; Kupfer, R; Troschitz, J; Homberg, W; Gude, M (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
Lightweight design by using low-density and load-adapted materials can reduce the weight of vehicles and the emissions generated during operation. However, the usage of different materials requires innovative joining technologies with increased versatility. In this investigation, the focus is on describing and characterising the failure behaviour of connections manufactured by an innovative thermomechanical joining process with adaptable auxiliary joining elements in single-lap tensile-shear tests. In order to analyse the failure development in detail, the specimens are investigated using in-situ computed tomography (in-situ CT). Here, the tensile-shear test is interrupted at points of interest and CT scans are conducted under load. In addition, the interrupted in-situ testing procedure is validated by comparing the loading behaviour with conventional continuous tensile-shear tests. The results of the in-situ investigations of joints with varying material combinations clearly describe the cause of failure, allowing conclusions towards an improved joint design.

In-situ CT of the clinching process – Influence of settling effects due to process interruptions - Köhler, D.; Kupfer, R.; Troschitz, J.; Gude, M. (Materials Research Proceedings)
Abstract. In lightweight constructions, clinching represents a cost-effective solution, in which joints are produced by local cold forming of the joining parts. Clinching phenomena are typically evaluated using destructive testing methods. While these methods influence the clinch point’s state, in-situ computed tomography (in-situ CT) is able to explore the clinching process with a specimen under load. Here, the path-controlled clinching process is interrupted at certain displacement levels and the specimen is scanned by CT while remaining in a stationary state. These interruptions are always accompanied by settling effects reducing the reaction force. Therefore, in this work, the influence of these interruptions on the force-displacement behavior during clinching and on the final clinch point’s geometric properties is investigated.

Experimentelle und numerische Analyse des Fließverhaltens von hochviskosen Wärmeleitstoffen im Fertigungsprozess - Gröger, Benjamin; Wiebicke, Felix; Koch, Ilja; Gude, Maik; Gilich, Julian; Meschut, Gerson (24. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Klebstoffmodell - Parameteridentifikation, Verifikation und Validierung für den Lastfall Crash - Beule, Felix; Teutenberg, Dominik; Meschut, Gerson (DECHEMA-Workshop für Klebstoffanwender: Simulation von Klebverbindungen)

Methodenentwicklung zur Simulation von hyperelastischen Klebverbindungen unter Crashbelastung - Beule, Felix; Teutenberg, Dominik; Meschut, Gerson; Schmelzle, Lars; Possart, Gunnar; Mergheim, Julia; Steinmann, Paul

Validierung von Methoden zur Vermeidung von Liquid Metal Embrittlement an realitätsnahen Prinzipbauteilen - Yang, Keke; Seitz, Georg; Schreiber, Vincent; Meschut, Gerson; Biegler, Max; Jüttner, Sven; Rethmeier, Michael

Corrosion behaviour of self-piercing riveted joints with uncoated rivets in high nitrogen steel - Uhe, Benedikt; Kuball, Clara-Maria; Merklein, Marion; Meschut, Gerson (Production Engineering)
Self-piercing riveting is an established joining technique for lightweight materials. To increase the sustainability of the rivet manufacturing process, the authors of the present paper have developed an approach for shortening the process chain by omitting the heat treatment and rivet coating. To do this, use is made of high nitrogen steel as the rivet material. Successful joining with these rivets has already been proven, and it has also been shown that a competitive joint strength can be achieved with these rivets. Up until now, no studies have been conducted of the corrosion behaviour of uncoated rivets in high nitrogen steel compared to conventional rivets made of heat-treatable steel with a coating of Almac® or zinc-nickel with topcoat, and the corrosion behaviour of joints manufactured with these rivets has also not been investigated. Furthermore, the suitability of rivets in high nitrogen steel for structures undergoing cathodic dip painting has not been evaluated to date. These are therefore the aims of the research work presented in this paper. Corrosion behaviour is tested by exposing rivets and joints to a salt spray atmosphere. Cross-cut tests are conducted in order to classify the adhesion of cathodic dip paint to the different rivet surfaces and materials. The results of the experimental test show that the cathodic dip paint has sufficient adhesion to the uncoated rivets in high nitrogen steel and that these rivets can therefore be used in the manufacture of car bodies. Due to the stainless properties of the high nitrogen steel, better corrosion resistance is seen by comparison to the commonly used coatings of Almac® and zinc-nickel with topcoat. A study of the corrosion behaviour of the joints shows that the rivet head diameter and rivet head position, in particular, are decisive for preventing crevice corrosion under the rivet head and contact corrosion within the joint.

Investigation of the influence of the rivet geometry on joint formation for a versatile self-piercing riveting process - Kappe, Fabian; Bobbert, Mathias; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part E: Journal of Process Mechanical Engineering)
Climate change has led to a large number of countries deciding to reduce carbon dioxide (CO 2 ) emissions significantly. As the mobility sector is a major contributor to CO 2 , various strategies are being pursued to achieve the climate targets set. An increasingly applied lightweight design method is the use of multi-material constructions. To join these structures, mechanical joining technologies such as self-pierce riveting are being used. As a result of the currently rigid tool systems, which cannot react to changing boundary conditions, a large number of rivet–die combinations is required to join the rising number of materials as well as material thickness combinations. Thus, new, versatile joining technologies are needed that can react to the described changes. The versatile self-piercing riveting (V-SPR) process is one possible approach. In this process, different material thicknesses can be joined by using a multi-range capable rivet which is set by a joining system with extended actuator technology. In this study, the V-SPR joining process is analysed numerically according to the influence of the geometrical rivet parameters on the joints characteristics as well as the resulting material flow. The investigations showed that the shank geometry has a decisive influence on the expansion of the rivet. Furthermore, the rivet length could be proven to be an influencing factor. By changing the head radii and the protrusion height, the forming behaviour of the rivet head onto the punch-sided joining part could be improved and thus the formation of air pockets was prevented. Based on the numerical investigations, a novel rivet geometry was developed and produced by machining. Subsequently, experimentally produced joints were analysed according to their joint formation and load-bearing capacity.

On the transferability of nominal surrogate models to uncertainty consideration of clinch joint characteristics - Bode, Christoph; Goetz, Stefan; Wartzack, Sandro (Procedia CIRP)

Influence of liquid metal embrittlement on the failure behavior of dissimilar spot welds with advanced high-strength steel: A component study - Yang, Keke; Sowada, Matthias; Olfert, Viktoria; Seitz, Georg; Schreiber, Vincent; Heitmann, Marcel; Hein, David; Biegler, Max; Jüttner, Sven; Rethmeier, Michael; Meschut, Gerson (Journal of Materials Research and Technology)

Analysis of the anisotropic mechanical properties of structural adhesive joints with curing-induced pre-deformations - Beule, Felix; Teutenberg, Dominik; Meschut, Gerson (Journal of Adhesion Science and Technology)

Investigation of the electrical quality and long-term stability of aluminum ground stud connections in automotive applications - Haak, Viktor; Yang, Keke; Meschut, Gerson (Journal of Advanced Joining Processes)
The rapid advancement in the electrification of modern vehicles has led to a continuous increase in electrical consumers for various comfort and safety functions. Ground studs serve as the electrical interface between the conductive vehicle body and the onboard network. Drawn arc stud welding is an economical and established joining process for producing ground stud joints. The circuits in the onboard network are increasingly subject to greater demands regarding current-carrying capacity and long-term stability. Reliable signal and power transmission require minimal contact resistance at the electrical connection points of the ground stud system and must withstand various operating and environmental conditions over the entire service life. In this study, a ground stud made of AlMg5, with a ZnNi-coated steel cap nut was used on a 2.0 mm thick sheet of AlMg3. The electrical connection of the ground studs was made using tinned copper cable lugs and 35 mm² cables. To analyze the electrical resistance behavior in an accelerated test, the ground studs were subjected to a superimposed load with a cyclic current profile for 1008 hours under changing climatic conditions. The results show that under the chosen operational and environmental conditions, accelerated aging and intermittent resistance behavior occur. A characteristic drop in resistance during the test indicates the failure point of the electrical connection. The cause of failure can be attributed to media penetration into the electrical contact zone. A failure of the electrical connection was observed after 512 hours.
Keywords: Stud welding; aluminum grounding connection; electrical resistance; superimposed load

Methodenentwicklung zur rechnerischen Auslegung geklebter Stahlverbindungen unter Alterungsbeanspruchung im Stahl- und Anlagenbau - Beule, Felix; Sander, Sascha; Meschut, Gerson; Damm, Jannis; Kasper, Yann; Albiez, Matthias; Kötz, Fabian; Matzenmiller, Anton (24. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

The influence of embedded fiber optic sensors on the global mechanical behavior of adhesively bonded joints - Hermelingmeier, Lucas; Aßmuth, Verena; Teutenberg, Dominik; Meschut, Gerson (77th IIW Annual Assembly and International Conference on Welding and Joining)

Development of a friction model for the numerical simulation of clinching processes - Böhnke, Max; Bielak, Christian Roman; Beck, Robert; Bobbert, Mathias; Meschut, Gerson (Friction)

Material Parameter Identification for a Stress-State-Dependent Ductile Damage and Failure Model Applied to Clinch Joining - Friedlein, Johannes; Böhnke, Max; Schlichter, Malte Christian; Bobbert, Mathias; Meschut, Gerson; Mergheim, Julia; Steinmann, Paul (Journal of Manufacturing and Materials Processing)
Similar to bulk metal forming, clinch joining is characterised by large plastic deformations and a variety of different 3D stress states, including severe compression. However, inherent to plastic forming is the nucleation and growth of defects, whose detrimental effects on the material behaviour can be described by continuum damage models and eventually lead to material failure. As the damage evolution strongly depends on the stress state, a stress-state-dependent model is utilised to correctly track the accumulation. To formulate and parameterise this model, besides classical experiments, so-called modified punch tests are also integrated herein to enhance the calibration of the failure model by capturing a larger range of stress states and metal-forming-specific loading conditions. Moreover, when highly ductile materials are considered, such as the dual-phase steel HCT590X and the aluminium alloy EN AW-6014 T4 investigated here, strong necking and localisation might occur prior to fracture. This can alter the stress state and affect the actual strain at failure. This influence is captured by coupling plasticity and damage to incorporate the damage-induced softening effect. Its relative importance is shown by conducting inverse parameter identifications to determine damage and failure parameters for both mentioned ductile metals based on up to 12 different experiments.

Low temperature debonding of toughened structural adhesive joints: A new approach to repairs in the automotive industry - Bartley, Aurélie; Chudalla, Nick; Meschut, Gerson; Wibbeke, Tim Michael (International Journal of Adhesion and Adhesives)

Untersuchung des Einflusses von Relativverschiebungen während der Aushärtung auf die mechanischen Eigenschaften von Klebverbindungen - Beule, Felix; Teutenberg, Dominik; Meschut, Gerson (Klebtechnische Doktorandenseminare 2020 - 2022)